Next-Gen Post-Diagnostic Care through Centralized AI and Smart Wearable Devices for Chronic Disease Management: A Narrative Review - Kumar, Gokul; Kumar, Prasanna (Indian Journal of Pharmaceutical Education and Research, 2025)
This article presents a futuristic framework for incorporating centralized AI to revolutionize patient care, focusing on the post-diagnostic care andmanagement of various chronic conditions.Through the integration of centralized AI with remote monitoring devices, smart wearables and home appliances, a futuristic approach to post-diagnostic care is proposed, serving diverse needs of patients with cardiovascular diseases, diabetes mellitus and sleep disturbances. By employing the power of AI, healthcare providers can deliver timely interventions, optimize treatment outcomes and enhance the overall quality of care for patients with chronic diseases. The Centralized AI system, equipped with advanced algorithms and extensive medical knowledge, facilitates personalized interventions, medication adherence reminders, lifestyle recommendations and continuous monitoring of physiological parameters. Using this centralized AI we can empower patients, support healthcare providers and ultimately improve the well-being and longevity of individuals living with chronic conditions.
Keywords: Artificial Intelligence; Smart wearables; Remote monitoring; Chronic disease management; Data analysis; Patient care management